2020
DOI: 10.1021/acs.est.9b07150
|View full text |Cite
|
Sign up to set email alerts
|

Stable Sulfur Isotopes Revealed a Major Role of Transition-Metal Ion-Catalyzed SO2Oxidation in Haze Episodes

Abstract: Secondary sulfate aerosols played an important role in aerosol formation and aging processes, especially during haze episodes in China. Secondary sulfate was formed via atmospheric oxidation of SO2 by OH, O3, H2O2, and transition-metal-catalyzed (TMI) O2. However, the relative importance of these oxidants in haze episodes was strongly debated. Here, we use stable sulfur isotopes (δ34S) of sulfate aerosols and a Rayleigh distillation model to quantify the contributions of each oxidant during a haze episode in N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
74
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(79 citation statements)
references
References 73 publications
4
74
1
Order By: Relevance
“…Some studies have suggested that oxidation by NO 2 would be enhanced by fog 9,13,17 . Aqueous-phase autoxidation of SO 2 by molecular oxygen catalyzed by transition metal ions (TMI) has been proposed 22,23 but is poorly constrained due to the lack of information on TMI concentration, complexation, and solubility 24 . A recent study suggests that aqueous-phase oxidation by hydrogen peroxide (H 2 O 2 ) in haze could be significant 10 .…”
mentioning
confidence: 99%
“…Some studies have suggested that oxidation by NO 2 would be enhanced by fog 9,13,17 . Aqueous-phase autoxidation of SO 2 by molecular oxygen catalyzed by transition metal ions (TMI) has been proposed 22,23 but is poorly constrained due to the lack of information on TMI concentration, complexation, and solubility 24 . A recent study suggests that aqueous-phase oxidation by hydrogen peroxide (H 2 O 2 ) in haze could be significant 10 .…”
mentioning
confidence: 99%
“…It can be found that the δ 34 Saerosol values showed a~3.9 ‰ variation, and displayed a negative correlation with SOR. The variation of δ 34 Saerosol values was attributed to the isotope fractionation during the oxidation processes of SO2 (Li et al, 2020). To shed light on the mechanism of SO2 oxidation in sulfur isotope fractionation and sulfate formation, the SO2 oxidation processes on the surface of α-Fe2O3 in the presence of NOX, O3, and NH3 were carried out in laboratory.…”
Section: Resultsmentioning
confidence: 99%
“…The δ 34 S value of SO2 sources (δ 34 Semission) strongly depends on the origin of SO2, thus it is difficult to constrain . On the basis of the literature, +2.7±2.0 ‰ is used as the δ 34 Semission value during our sampling period (Li et al, 2020). Therefore, we used a Rayleigh distillation model and the isotopic enrichment factor (ԑ = (α-1)*1000‰) to explain the discrepancy between δ 34 S and δ 34 Semission values and quantify the contributions of each oxidant on the basis of the above results in the experiment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HiFA increases HCHO emissions from the transportation and residential sectors by a factor of 5. Chemical transport models commonly underestimate SO 4 2− during winter haze episodes in China, and thus some studies have adopted an apparent heterogeneous parameterization for SO2 reactive uptake in order to compensate for the missing SO 4 2− (Zheng et al, 2015;Cheng et al, 2016;Wang et al, 2016;Liu et al, 2019;Li et al, 2020).…”
Section: Sensitivity Simulationsmentioning
confidence: 99%